The effect of a high fructose diet and glucocorticoids intervention on cardiac structure and function in male Sprague Dawley rats - Mokoena, Thobekile Sibonelo (My University, 2024)
The impact of glucocorticoids on left ventricular (LV) morphology and function in animal models and their interaction with metabolic syndrome (MetS) remain unclear. This study aimed to determine the effects of glucocorticoids on LV structure and function and whether MetS exacerbates these effects. Male Sprague Dawley rats were assigned to control, glucocorticoids (GC), high fructose (HF) and glucocorticoids + high fructose (GC+HF) groups (n=10each). HF and GC+HF groups received a 20% fructose solution, while GC and GC+HF groups received 10mg/kg intraperitoneal injections of methylprednisolone daily for 10 weeks. After 10 weeks, LV function was assessed, and cardiac collagen content was determined. Relative wall thickness was greater in the GC group compared to the control (p=0.01). The heart weight indexed to body mass, LV weight indexed to body mass and the relative wall thickness were greater in the GC+HF compared to the control (p=0.04; p=0.009; and p=0.01 respectively). The LV end-diastolic volume was lower in the GC+HF group compared to the control (p=0.007) and the HF(p=0.01). The lateral e’ was lower in the GC and GC+HF groups compared to the control (p=0.001 and p=0.005 respectively) and HF (p<0001 and p=0.0001). The E/e’ was greater in GC and GC+HF rats compared to control (p<0.0001 and p=0.004, respectively) and HF (p<0.0001 and p=0.02, respectively). Cardiac collagen content was greater in GC and GC+HF groups compared to control (p=0.001 and p<0.0001 respectively). In conclusion, glucocorticoid administration induced cardiac remodelling, impaired LV relaxation and increased LV diastolic filling pressures. The presence of MetS resulted in concentric hypertrophy, but did not worsen LV diastolic dysfunction.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, School of Physiology, Johannesburg, 2023
Keywords: Glucocorticoids; Male Sprague Dawley rats; High fructose